CHALLENGES OF EDUCATION MANAGEMENT SYSTEM IN ELEMENTARY SCHOOLS AND SOLVING STRATEGIES - Yeyen Fitri; Siti Inganah (RADJA PUBLIKA, 2025)
This qualitative descriptive research aims to understand the challenges of the education management system in primary schools and the strategies implemented to address them. The study focuses on five public primary schools in Musi Rawas Regency, South Sumatra, involving school principals, teachers, school committees, and education supervisors as research subjects. Data were collected through in-depth interviews, participatory observations, and documentation. Data analysis employed Miles' interactive model (1994), which includes data reduction, data display, and conclusion drawing. The findings reveal several main challenges: centralized leadership by school principals, low involvement of school committees and parents, inconsistent government policies, and limited resources and infrastructure. Nevertheless, the research also identified several strategies implemented by schools to address these issues, including strengthening transformational leadership, revitalizing the role of school committees, adapting policies through a local approach, and gradually using technology. It is recommended that primary school education management emphasize participatory approaches, inclusive leadership enhancement, empowerment of school committees and parents, and the development of more consistent and contextual education policies.